CBCT Evaluation of the maxillary palatine process as a donor site for the regeneration of periodontal defects - Yaser Safi; Sepideh Behzadi; Marziyeh Shafizadeh; Reza Amid; Mahdi Kadkhodazadeh (Tabriz University of Medical Sciences, 2022)
Background. The maxillary palatine process (MPP) is an excellent source of autogenous bone transplants for anterior maxillary reconstruction. This research aimed to determine the quantity and quality of accessible MPP as a donor location. Methods. Cone-beam computed tomography (CBCT) scans of patients referred to the School of Dentistry were evaluated by a certified examiner. The harvestable MPP was defined as the space between the distal surfaces of maxillary first premolars. OnDemand 3D Imaging software was used to determine bone properties. SPSS software was used to investigate the following variables: Bone characteristics are correlated with age and gender, accessible volume, and palatal width and height. P<0.05 was defined as the level of statistical significance. Results. This study was performed on CBCT scans of 81 subjects (41 females and 40 males). MPP volume and palatal heights were 1.33±0.53 cm3 and 20.86±5.51 mm, respectively. Maximum bone density was observed around lateral incisors. Palatal width was 33.81±2.42 mm between canines and 41.81±2.66 mm between premolars. The MPP volume was significantly greater in males (P<0.001). Additionally, there was a positive correlation between the volume and palatal width (P<0.05). Conclusion. Within the constraints of this research, there is a limited supply of MMP accessible for use as a graft source, and it is best suited for treating localized bone lesions. The favorable link between palatal breadth and harvestable volume aids the surgeon in estimating the quantity of bone accessible during the first evaluation.